High-stability electrode for electrochemical lithium extraction and preparation method thereof
By covering the solid electrolyte and organic conductive polymer on the surface of the electrochemical lithium extract electrode, forming a double-layer coated structure, the problems of poor cycle stability and low current efficiency of the electrode in alkaline brine are solved, and high-efficiency lithium ions are achieved Lithium extraction.
Patent Information
- Application Number
- CN202411573789.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing electrochemical lithium extraction technology, the electrode has poor cycle stability, low current density and low current efficiency in alkaline brine, resulting in low efficiency in the lithium extraction process.
A high-stability electrode is adopted to form a double-layer clad structure by covering the surface of the active material to improve the cyclic stability and current density of the electrode.
It effectively improves the cyclic stability and current density of the electrode in alkaline brine, improves the current efficiency of the lithium extraction process, is highly adaptable, is cheap and is easy to produce in industrialized production.
Smart Images

Figure CN119433234A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium resource extraction, and in particular to a high-stability electrode for electrochemical lithium extraction and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy vehicle industry, the demand for lithium salt products in power batteries is increasing day by day, resulting in an increasingly prominent contradiction between the supply and demand of lithium salt. Lithium resources are mainly found in granite pegmatite, salt lake brine, underground brine and seawater, and the lithium resources in salt lake brine account for about 70% of the world's total lithium resources. Therefore, how to efficiently develop lithium resources in salt lake brine is of great significance to alleviating the contradiction between the supply and demand of lithium salt and promoting the healthy development of the new energy vehicle industry.
[0003] At present, the main technologies for extracting lithium from salt lake brine include precipitation, extraction, electrodialysis, adsorption and electrochemical methods. The precipitation method is suitable for treating salt lake brine with a low magnesium-to-lithium ratio and has a simple process; the extraction method can efficiently extract lithium from brine, and a high-concentration lithium-rich solution can be obtained after stripping, but it is urgent to develop an extractant with low or even no dissolution loss; the electrodialysis method can effectively treat old brine and achieve efficient separation of lithium and multivalent ions, but it is urgent to achieve domestic substitution of membranes; the adsorption method can selectively adsorb lithium from brine with lower concentrations, and a lithium-rich solution can be obtained after desorption, but the capacity and stability of the adsorbent need to be further optimized. The electrochemical lithium extraction technology can treat salt lake brine at different stages and different lithium concentrations, and the lithium extraction process does not use acid-base reagents or produce acid or alkali, which can achieve green and pollution-free extraction of lithium resources in brine.
[0004] Salt lakes can be divided into sulfate salt lakes, chloride salt lakes and carbonate salt lakes according to the difference in their brine composition. The presence of a large number of carbonate ions in carbonate salt lakes makes their brine alkaline (the pH of the brine is about 8.5-9.5). When polyanion materials (such as lithium iron phosphate) are used as active materials for electrochemical lithium extraction, they have good cycle stability in sulfate and chloride salt lake brines (the pH of the brine is neutral), while their cycle stability is significantly reduced in carbonate salt lake brines (the pH of the brine is alkaline). The reason is that lithium iron phosphate is prone to generate lithium phosphate and iron hydroxide when electrochemical lithium extraction is carried out under alkaline conditions, which leads to capacity decay and decreased cycle stability. In addition, the high mineralization and high viscosity of brine make it difficult for brine to transfer mass inside the electrode, resulting in a large concentration difference between lithium ions inside the electrode material and in the brine. The concentration of impurity ions in brine is about dozens or even hundreds of times that of lithium ions. Cathodic polarization is likely to occur during the lithium extraction process, resulting in decreased electrode selectivity and current efficiency during electrochemical lithium extraction. Therefore, how to improve the stability and selectivity of electrodes during electrochemical lithium extraction is crucial for the industrial application of electrochemical lithium extraction technology. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high-stability electrode for electrochemical lithium extraction and a preparation method thereof, so as to solve at least one of the problems of poor cycle stability, low current density, and low current efficiency of electrodes prepared by existing methods.
[0006] In a first aspect, the present invention provides a high-stability electrode for electrochemical lithium extraction, comprising a current collector, wherein the surface of the current collector is coated with an active material, a conductive agent, an additive and a pore-forming agent, and the active material is a polyanion material;
[0007] The surface of the polyanion material is coated with a solid electrolyte and an organic conductive polymer in sequence from the inside to the outside;
[0008] Or the surface of the polyanion material is coated with an organic conductive polymer and a solid electrolyte in sequence from the inside to the outside.
[0009] Furthermore, the solid electrolyte is at least one of a garnet-type, peroxide-type, sodium superion conductor or lithium superion conductor solid electrolyte.
[0010] Furthermore, the solid electrolyte is Li7La3Zr2O 12 , Li 0.33 La 0.56 At least one of TiO3, LiTi2(PO4)3 or Li2SiO3.
[0011] Furthermore, the organic conductive polymer is polymerized from conductive polymer monomers. Preferably, the conductive polymer monomer is at least one of pyrrole, aniline and thiophene.
[0012] Furthermore, the polyanion material is a water-soluble lithium-ion battery material. Preferably, the polyanion material is LiFePO4OH, LiFePO4F, LiFe x Mn 1-x At least one of PO4 (0<x<1), LiFePO4.
[0013] Furthermore, the conductive agent is at least one of acetylene black, carbon nanotubes, super P, Ketjen black, carbon fiber, and graphene;
[0014] And / or, the additive is at least one of polyethylene glycol and polyvinyl alcohol;
[0015] And / or, the pore-forming agent is at least one of sodium sulfate, potassium sulfate, magnesium chloride, magnesium sulfate, calcium chloride, and barium chloride.
[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned electrode, comprising the following steps:
[0017] (1) mixing a polyanion material with a solid electrolyte precursor solution to react, and evaporating to obtain an active material in situ coated with a solid electrolyte;
[0018] Or the polyanion material is mixed with the conductive polymer monomer, an oxidant is added to carry out polymerization reaction, and then dried to obtain an active material coated with an organic polymer;
[0019] (2) mixing the active material coated in situ by the solid electrolyte with a conductive polymer monomer, adding an oxidant to carry out polymerization reaction, and drying to obtain a double-layer coated active material;
[0020] or mixing the organic polymer coated active material with a solid electrolyte precursor solution to react and evaporate to obtain a double-layer coated active material;
[0021] (3) Premixing the double-layer coated active material with a conductive agent, an additive, and a pore-forming agent, adding N-methylpyrrolidone dissolved with PVDF, mixing to obtain a slurry, and coating the slurry on a current collector to obtain the electrode.
[0022] Furthermore, in steps (1) and (2), the concentration of the solid electrolyte precursor solution is 0.1 to 3 mol / L.
[0023] Furthermore, in step (3), premix for 2 to 8 hours, add PVDF dissolved in N-methylpyrrolidone (NMP) in 3 to 5 portions, and mix for 2 to 6 hours.
[0024] Furthermore, in step (3), the mass ratio of the double-layer coated active material, the conductive agent, the additive, the pore-forming agent and the PVDF is 1:0.05-0.15:0.01-0.05:0.1-0.5:0.05-0.15.
[0025] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0026] (1) The electrode of the present invention is coated with a solid electrolyte on the surface of the active material. The coating layer can effectively avoid direct contact between brine and the active material, prevent the occurrence of side reactions, and thus improve the cycle stability of the electrode. The solid electrolyte layer has the function of transmitting lithium ions, which can achieve the interception of impurity ions and improve the electrode's selectivity for lithium ions. The active material of the present invention is also coated with an organic conductive polymer. The organic conductive polymer layer can effectively improve the electronic conductivity of the active material, reduce the charge transfer impedance of the active material, and achieve high current density lithium extraction;
[0027] (2) The polyanion material selected in the present invention not only has the characteristics of stable lattice structure and lithium ion transport migration channel, but also has a stable electrochemical working window in aqueous solution. The polyanion active material can achieve selective insertion and extraction of lithium ions by controlling the redox potential of the electrode during the electrochemical lithium extraction process;
[0028] (3) The preparation method of the electrode of the present invention first pre-mixes the polyanion active material double-coated with the conductive polymer and the solid electrolyte, the conductive agent, the additive, and the pore-forming agent by ball milling to obtain a highly dispersed slurry, and the batch addition of the NMP solvent can realize the controllable viscosity of the slurry, thereby ensuring the controllability of the slurry viscosity, thereby preparing an electrode for lithium extraction with good performance, high strength, and stable structure;
[0029] (4) The electrode brine prepared by the method of the present invention has strong adaptability, good cycle stability, simple preparation method, low cost, and is easy to mass industrialize.
[0030] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0032] Figure 1 This is a graph showing the lithium extraction performance of the electrode prepared in Example 2 of the present invention;
[0033] Figure 2 This is a graph showing the change in current efficiency of the electrode prepared in Example 3 of the present invention during the lithium extraction process as a function of the lithium extraction cycle;
[0034] Figure 3 This is a graph showing the cycle performance of the electrodes prepared in Example 5, Example 5-1 and Comparative Examples 1-4 of the present invention during the lithium extraction process. DETAILED DESCRIPTION
[0035] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0036] A specific embodiment of the present invention discloses a high-stability electrode for electrochemical lithium extraction, comprising a current collector, the surface of which is coated with an active material, a conductive agent, an additive and a pore-forming agent, wherein the active material is a polyanion material;
[0037] The surface of the polyanion material is coated with a solid electrolyte and an organic conductive polymer in sequence from the inside to the outside;
[0038] Or the surface of the polyanion material is coated with an organic conductive polymer and a solid electrolyte in sequence from the inside to the outside.
[0039] Compared with the prior art, the electrode of the present invention is coated with a solid electrolyte on the surface of the active material. The coating layer can effectively avoid direct contact between brine and the active material, prevent the occurrence of side reactions, and thus improve the cycle stability of the electrode. The solid electrolyte layer has the function of transmitting lithium ions, which can achieve the interception of impurity ions and improve the selectivity of the electrode for lithium ions. The active material of the present invention is also coated with an organic conductive polymer, and the organic conductive polymer layer can effectively improve the electronic conductivity of the active material, reduce the charge transfer impedance of the active material, and achieve high current density lithium extraction.
[0040] Preferably, the active material, the conductive agent, the additive, and the pore-forming agent are dissolved in N-methylpyrrolidone containing PVDF to prepare a slurry, and then the slurry is coated on the current collector.
[0041] In a specific embodiment, the solid electrolyte is at least one of a garnet-type, peroxide-type, sodium superion conductor (NASICON) or lithium superion conductor (LISICON) solid electrolyte.
[0042] Preferably, the solid electrolyte is Li7La3Zr2O 12 (LLZO), Li 0.33 La 0.56 At least one of TiO3(LLTO), LiTi2(PO4)3 or Li2SiO3. The solid electrolyte selected by the present invention is an excellent conductor of lithium ions, which can effectively transmit lithium ions and improve the selectivity of electrode materials to lithium.
[0043] In a specific embodiment, the organic conductive polymer is polymerized from conductive polymer monomers. Preferably, the conductive polymer monomer is at least one of pyrrole, aniline and thiophene.
[0044] In a specific embodiment, the polyanion material is a water-soluble lithium-ion battery material. Preferably, the polyanion material is LiFePO4OH, LiFePO4F, LiFe x Mn 1-xAt least one of PO4 (0<x<1), LiFePO4.
[0045] It should be noted that since the electronic conductivity of polyanion active materials is generally low and the charge transfer impedance is high. Coating the polyanion active materials with conductive polymers can not only improve the electronic conductivity of the polyanion active materials, but also provide a stable reaction interface for electrochemical reactions. The polyanion materials selected in the present invention not only have the characteristics of stable lattice structure and lithium ion transmission and migration channels, but also have a stable electrochemical working window in aqueous solution. The polyanion active materials can achieve selective insertion and extraction of lithium ions by controlling the redox potential of the electrodes during the electrochemical lithium extraction process.
[0046] In a specific embodiment, the conductive agent is at least one of acetylene black, carbon nanotubes, super P, Ketjen black, carbon fiber, and graphene;
[0047] And / or, the additive is at least one of polyethylene glycol and polyvinyl alcohol;
[0048] And / or, the pore-forming agent is at least one of sodium sulfate, potassium sulfate, magnesium chloride, magnesium sulfate, calcium chloride, and barium chloride.
[0049] In order to make the prepared electrode have higher water absorption and wettability, a pore-forming agent is added during the slurry preparation process. The pore-forming agent is a water-soluble inorganic salt that can be dissolved after being immersed in water, thereby making the electrode surface have more micropores.
[0050] In a specific embodiment, the current collector is at least one of a titanium mesh, a titanium plate, a titanium foil, a carbon fiber cloth, and a carbon felt.
[0051] The present invention discloses a method for preparing the above-mentioned electrode, comprising the following steps:
[0052] (1) mixing a polyanion material with a solid electrolyte precursor solution to react, and evaporating to obtain an active material in situ coated with a solid electrolyte;
[0053] Or the polyanion material is mixed with the conductive polymer monomer, an oxidant is added to carry out polymerization reaction, and then dried to obtain an active material coated with an organic polymer;
[0054] (2) mixing the active material coated in situ by the solid electrolyte with a conductive polymer monomer, adding an oxidant to carry out polymerization reaction, and drying to obtain a double-layer coated active material;
[0055] or mixing the organic polymer coated active material with a solid electrolyte precursor solution to react and evaporate to obtain a double-layer coated active material;
[0056] (3) Premixing the double-layer coated active material with a conductive agent, an additive, and a pore-forming agent, adding N-methylpyrrolidone dissolved with PVDF, mixing to obtain a slurry, and coating the slurry on a current collector to obtain the electrode.
[0057] It should be noted that in the method of the present invention, since the solid electrolyte has good ionic conductivity, lithium ions can be efficiently transmitted, while most impurity ions are difficult to pass through the solid electrolyte coating layer. At the same time, coating a layer of solid electrolyte can improve the selectivity of the active material for lithium ions and improve the current efficiency. In addition, direct contact between brine and active materials can be avoided, thereby improving the cycle stability of electrode materials in brine, especially in alkaline brine. In order to achieve effective coating of the solid electrolyte on the surface of the active material, a solid electrolyte precursor solution is required to be used to in-situ coat the surface of the active material.
[0058] In a specific embodiment, in steps (1) and (2), the concentration of the solid electrolyte precursor solution is 0.1 to 3 mol / L, for example, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L, 0.9 mol / L, 1.1 mol / L, 1.3 mol / L, 1.5 mol / L, 1.7 mol / L, 1.9 mol / L, 2.1 mol / L, 2.3 mol / L, 2.5 mol / L, 2.7 mol / L, 2.9 mol / L, 3.0 mol / L. If the concentration is low, the coating amount is insufficient and the material cannot be effectively coated; if the concentration is high, the capacity of the electrode material is affected.
[0059] In a specific embodiment, in step (1), the polyanion material and the solid electrolyte precursor solution are mixed and reacted at a solid-liquid ratio of 1:5 to 50 (for example, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50) for 0.5 to 10 h (for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h);
[0060] If the liquid-to-solid ratio is too low, the coating amount is insufficient and the material cannot be effectively coated; if it is too high, it will affect the capacity of the electrode material.
[0061] Or the mass of the conductive polymer monomer is 0.05 to 2 times the mass of the polyanion material, for example, 0.05 times, 0.1 times, 0.2 times, 0.3 times, 0.4 times, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, 1.0 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, 2 times. If it is too low, the coating is not good, and if it is too high, the cost is high, the proportion of effective substances is reduced, thereby reducing the adsorption capacity.
[0062] Specifically, in steps (1) and (2), the polymerization reaction time is 2 to 6 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours. If the polymerization time is short, the polymerization is not thorough and the coating effect is not ideal; if the time is too long, the production efficiency is affected.
[0063] In a specific embodiment, in step (2), the mass of the conductive polymer monomer is 0.05 to 2 times the mass of the active material in situ coated by the solid electrolyte, for example, 0.05 times, 0.1 times, 0.2 times, 0.3 times, 0.4 times, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, 1.0 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, 2 times;
[0064] Or the organic polymer-coated active material and the solid electrolyte precursor solution are mixed and reacted at a solid-to-liquid ratio of 1:5 to 50 (for example, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50) for 0.5 to 10 h (for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h).
[0065] In a specific embodiment, in step (3), premix for 2 to 8 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, and 8 hours, and add PVDF dissolved in N-methylpyrrolidone (NMP) in 3 to 5 times and mix for 2 to 6 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours.
[0066] It should be noted that in order to achieve controllable viscosity of the slurry and make the slurry have good bonding properties, the NMP solvent containing the binder PVDF is added to the premixed slurry in 3 to 5 times.
[0067] In a specific embodiment, in step (3), the mass ratio of the double-layer coated active material, the conductive agent, the additive, the pore-forming agent and the PVDF is 1:0.05-0.15:0.01-0.05:0.1-0.5:0.05-0.15.
[0068] Preferably, the mass of the N-methylpyrrolidone is 0.5 to 2 times the total mass of the double-layer coated active material, conductive agent, additive, pore-forming agent and PVDF, for example, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, 1 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, and 2 times.
[0069] It should be noted that the total mass of the double-layer coated active material, conductive agent, additive, pore-forming agent and PVDF described in the present invention is the mass of all solids. In order to ensure that the prepared electrode has good water absorption, wettability and lithium extraction performance, the added amount of the polyanion active material, conductive agent, additive and pore-forming agent doubly coated with the conductive polymer and the solid electrolyte needs to be effectively regulated; if the added amount is too small, it is not conducive to the performance of the electrode, and if the added amount is too large, it is easy to cause waste of raw materials.
[0070] In order to obtain a uniformly dispersed slurry, the conductive polymer and solid electrolyte dual-coated polyanion active material is fully premixed with the conductive agent, additive and pore former, so that the conductive polymer and solid electrolyte dual-coated polyanion active material is evenly dispersed and in good contact with the conductive agent, additive and pore former.
[0071] The slurry prepared by the above method can obtain a slurry with uniform dispersion, controllable viscosity and good adhesion, thereby improving the structural stability of the electrode. In addition, adding a pore-forming agent during the slurry preparation process can make the electrode surface have more micropores or microcracks, which can improve the hydrophilicity of the electrode and reduce the concentration range of the lithium extraction process.
[0072] The electrode brine prepared by the method of the present invention has strong adaptability, good cycle stability, simple preparation method, low cost and is easy for mass industrial production.
[0073] The average current efficiency of the electrode of the present invention is greater than 89.98%, and the average current density is greater than 30A / m 2 .
[0074] The technical solution of the present invention is further explained below in conjunction with specific embodiments. The raw materials used in the present invention are all commercially available raw materials.
[0075] Example 1
[0076] A high stability electrode for electrochemical lithium extraction in this embodiment is prepared by the following method:
[0077] (1) Add LiFePO4F to 0.1 mol / L Li7La3Zr2O 12 (LLZO) precursor solution, the precursor solution is prepared by mixing lithium acetate, lanthanum acetate and tetrabutyl zirconate in a stoichiometric ratio, the solid-liquid ratio is controlled to be 1:50 and the reaction is carried out for 3 hours, and after evaporating the solvent, LLZO in-situ coated LiFePO4F (i.e., LiFePO4F@LLZO) is obtained;
[0078] (2) mixing the LiFePO4F@LLZO obtained in step (1) with a pyrrole monomer solution, and then adding an oxidant, ferric chloride, to react for 6 hours, wherein the mass of the pyrrole monomer solution is 0.05 times the mass of LiFePO4F@LLZO, and then obtaining LiFePO4F (i.e., LiFePO4F@LLZO@PPy) doubly coated with a conductive polymer polypyrrole (PPy) and LLZO;
[0079] (3) The LiFePO4F@LLZO@PPy obtained in step (2) was mixed with acetylene black, carbon nanotubes, polyethylene glycol, and sodium sulfate in a mass ratio of 1:0.10:0.05:0.01:0.5 by ball milling for 8 hours, and then NMP containing PVDF was added to the above mixture in three portions, and the mixture was fully mixed for 2 hours to obtain a slurry, wherein PVDF was 0.1 times the mass of LiFePO4F@LLZO@PPy and NMP was 1 times the mass of all solids; the slurry was evenly coated on a titanium mesh, and the LiFePO4F@LLZO@PPy electrode was obtained after drying.
[0080] A Li 1+x Preparation of FePO4F@LLZO@C (0<x<1) electrode: 1+ x The FePO4F@LLZO@PPy electrode was used as the cathode and the nickel foam was used as the anode. The cathode and cathode were placed in a Li2SO4 solution containing a lithium concentration of 2 g / L. A voltage of 0.8 V was applied across the electrodes until the current density was lower than 0.5 A / m 2 , obtain Li 1+x FePO4F@LLZO@PPy electrode.
[0081] In the lithium extraction experiment of this example, the electrochemical lithium extraction device was separated into a cathode chamber and an anode chamber by using a monovalent anion selective permeable membrane. 1+xThe FePO4F@LLZO@PPy electrodes were used as cathode and anode, and were placed in the anode chamber and cathode chamber, respectively. 20L of salt lake brine was injected into the cathode chamber. The brine composition is shown in Table 1 below. 2L of 5g / L NaCl solution was injected into the anode as a supporting electrolyte. A voltage of 0.35V was applied to the anode and cathode. After 6 hours of electrolysis, the lithium concentration in the brine decreased to 0.12g / L; the lithium concentration in the anode lithium-rich solution increased to 5.39g / L, and the average current efficiency reached 90.91%. The anode and cathode electrodes after lithium extraction were swapped, and 20L of brine and 2L of sodium chloride solution were re-injected and powered on to extract lithium. Keeping all conditions unchanged, after 6 hours of continuous electrolysis, the lithium concentration of the brine decreased to 0.11g / L, the lithium concentration in the anode lithium-rich solution reached 5.53g / L, the average current efficiency reached 90.42%, and the average current density was 31.25A / m 2 .
[0082] Table 1 Main components of brine used in Example 1
[0083] ion <![CDATA[Li + ]]> <![CDATA[Na + ]]> <![CDATA[K + ]]> <![CDATA[Mg 2+ ]]> <![CDATA[SO4 2- ]]> <![CDATA[B4O7 2- ]]> Concentration (g / L) 0.61 51.23 5.02 21.25 12.43 3.26
[0084] Cyclic lithium extraction experiment: A diaphragm-free electrochemical lithium extraction device was used to conduct a cyclic lithium extraction experiment. 1+x The FePO4F@LLZO@PPy electrode and the LiFePO4F@LLZO@PPy electrode were used as the anode and cathode respectively, and were placed in a lithium extraction device and powered on for a cyclic lithium extraction experiment. The cycle results showed that the LiFePO4F@LLZO@PPy electrode had good cycle stability. After 300 cycles, its capacity still reached 24.88 mg / g, and the capacity retention rate was as high as 90.23%.
[0085] Example 2
[0086] A high stability electrode for electrochemical lithium extraction in this embodiment is prepared by the following method:
[0087] (1) Add LiFePO4OH to 0.5 mol / L Li 0.33 La 0.56 In the TiO3 (LLTO) precursor solution, the precursor solution is mixed with LiOH·H2O, La(NO3)3·6H2O, and tetrabutyl titanate in a stoichiometric ratio, and the solid-liquid ratio is controlled to be 1:30 for 10 hours. After evaporating the solvent, LLTO in-situ coated LiFePO4OH (i.e., LiFePO4OH@LLTO) is obtained;
[0088] (2) mixing the LiFePO4OH@LLTO obtained in step (1) with an aniline monomer solution, and then dropping hydrogen peroxide to carry out polymerization reaction for 3 hours, wherein the mass of the aniline monomer is 0.2 times the mass of LiFePO4OH@LLTO, and then obtaining LiFePO4OH doubly coated with a conductive polymer polyaniline (PANI) and LLTO (i.e., LiFePO4OH@LLTO@PANI);
[0089] (3) The LiFePO4OH@LLTO@PANI obtained in step (2) was mixed with super P, carbon nanotubes, polyvinyl alcohol, and potassium sulfate in a ratio of 1:0.05:0.05:0.03:0.4 by ball milling for 8 hours, and then NMP containing PVDF was added to the above mixture in 4 portions. After thorough mixing for 2 hours, a slurry was obtained, in which PVDF was 0.15 times the mass of LiFePO4OH@LLTO@PANI and NMP was 1.5 times the mass of all solids; the slurry was evenly coated on a titanium plate and dried to obtain a LiFePO4OH@LLTO@PANI electrode.
[0090] A Li 1+x Preparation of FePO4OH@LLTO@PANI (0<x<1) electrode: The prepared LiFePO4OH@LLTO@PANI electrode was used as the cathode and the graphite plate was used as the anode. The cathode and cathode were placed in a LiCl solution containing a lithium concentration of 2 g / L. A voltage of 1.2 V was applied to both ends of the electrode through an external circuit until the current density was lower than 0.5 A / m 2 , obtain Li 1+ x FePO4OH@LLTO@PANI electrode.
[0091] Lithium extraction experiment: The electrochemical lithium extraction device was separated into a cathode chamber and an anode chamber using a monovalent anion selective permeable membrane. 1+x The FePO4OH@LLTO@PANI electrode and LiFePO4OH@LLTO@PANI electrode were used as the anode and cathode, respectively, and were placed in the anode chamber and cathode chamber, respectively. 30L of carbonate salt lake brine was injected into the cathode chamber. The brine composition is shown in Table 2 below. 2L of 1g / L LiCl solution was injected into the anode as a supporting electrolyte. A voltage of 0.3V was applied to the cathode and cathode through an external circuit. After 5 hours of electrolysis, the lithium concentration of the brine decreased to 0.08g / L; the lithium concentration in the anode lithium-rich solution increased to 4.58g / L, the average current efficiency reached 91.70%, and the average current density was 31.79A / m 2 .
[0092] Table 2 Main components of brine used in Example 2
[0093] ion <![CDATA[Li + ]]> <![CDATA[Na + ]]> <![CDATA[K + ]]> <![CDATA[CO3 2- ]]> <![CDATA[SO4 2- ]]> <![CDATA[B4O7 2- ]]> Concentration (g / L) 0.36 56.23 10.02 13.25 15.13 4.31
[0094] Cyclic lithium extraction experiment: A diaphragm-free electrochemical lithium extraction device was used to conduct a cyclic lithium extraction experiment. 1+x The FePO4OH@LLTO@PANI electrode and the LiFePO4OH@LLTO@PANI electrode were used as the anode and cathode, respectively, and were placed in a lithium extraction device and powered on for a cyclic lithium extraction experiment. The cyclic performance of the LiFePO4OH@LLTO@PANI electrode is shown in Figure 2. Figure 1 As shown, from Figure 1 It can be seen that LiFe PO4OH@LLTO@PANI has good cycle stability. After 200 cycles, the capacity of the electrode still reaches 23.69 mg / g, and the capacity retention rate is as high as 89%.
[0095] Example 3
[0096] A high stability electrode for electrochemical lithium extraction in this embodiment is prepared by the following method:
[0097] (1) adding LiFePO4F to a 3 mol / L LiTi2(PO4)3 precursor solution, wherein the precursor solution is a mixture of lithium acetate, ammonium dihydrogen phosphate and tetrabutyl titanate in a chemical ratio, controlling the solid-liquid ratio to be 1:5 and reacting for 3 h, and evaporating the solution to obtain LiTi2(PO4)3 in-situ coated LiFePO4F (i.e., LiFePO4F@LiTi2(PO4)3);
[0098] (2) mixing the LiFePO4F@LiTi2(PO4)3 obtained in step (1) with a thiophene monomer solution, and then dropping an ammonium persulfate solution to carry out a polymerization reaction for 2 hours, wherein the mass of the aniline monomer is 0.1 times the mass of the LiFePO4F@LiTi2(PO4)3, and then obtaining LiFePO4F (i.e., LiFePO4F@LiTi2(PO4)3@PTh) doubly coated with a conductive polymer polythiophene (PTh) and LiTi2(PO4)3;
[0099] (3) The LiFePO4F@LiTi2(PO4)3@PTh obtained in step (2) is mixed with Ketjen black, carbon fiber, polyethylene glycol, and magnesium chloride in a ratio of 1:0.05:0.05:0.03:0.4 by ball milling for 2 hours, and then NMP containing PVDF is added to the above mixture in 5 portions, and the mixture is fully mixed for 6 hours to obtain a slurry, wherein PVDF is 0.1 times the mass of LiFePO4F@LiTi2(PO4)3@PTh, and NMP is 0.5 times the mass of all solids; the slurry is evenly coated on a titanium plate, and a LiFePO4F@LiTi2(PO4)3@PTh electrode is obtained after drying.
[0100] A Li 1+x Preparation of FePO4F@LiTi2(PO4)3@PTh ((0<x<1)) electrode: The prepared LiFePO4F@LiTi2(PO4)3@PTh electrode was used as the cathode and the graphite plate as the anode. The cathode and cathode were placed in a LiCl solution containing a lithium concentration of 2g / L. A voltage of 1.0V was applied to both ends of the electrode through an external circuit until the current density was lower than 0.5A / m 2 , obtain Li 1+x FePO4F@LiTi2(PO4)3@PTh electrode.
[0101] Lithium extraction experiment: The electrochemical lithium extraction device was separated into a cathode chamber and an anode chamber using a monovalent anion selective permeable membrane. 1+x The FePO4F@LiTi2(PO4)3@PTh electrode and the LiFe PO4F@LiTi2(PO4)3@PTh electrode were used as the anode and cathode, respectively, and were placed in the anode chamber and cathode chamber, respectively. 20L of the same salt lake brine as in Example 1 was injected into the cathode chamber, and 2L of 1g / L LiCl solution was injected into the anode as a supporting electrolyte. A voltage of 0.3V was applied to the cathode and cathode through an external circuit. After 5 hours of electrolysis, the lithium concentration of the brine decreased to 0.09g / L; the lithium concentration in the lithium-rich solution at the anode increased to 5.65g / L, the average current efficiency reached 92.04%, and the average current density was 32.67A / m 2 .
[0102] Cyclic lithium extraction experiment: Switch the cathode and anode, re-inject brine and supporting electrolyte of the same volume and composition, and conduct a cyclic lithium extraction experiment. The current efficiency changes with the lithium extraction cycle during the lithium extraction process. Figure 2 As shown. Figure 2 It can be seen that in the multiple lithium extraction processes, when the LiFePO4F@LiTi2(PO4)3@PTh electrode is used for electrochemical lithium extraction, the average current efficiency is above 90%, indicating that the electrode material can still maintain good lithium selectivity after multiple cycles of lithium extraction.
[0103] Example 4
[0104] A high stability electrode for electrochemical lithium extraction in this embodiment is prepared by the following method:
[0105] (1) LiFe x Mn 1-x PO4 (0<x<1) powder is mixed with pyrrole monomer solution, and then ferric chloride is added dropwise to carry out polymerization reaction for 4 hours. The mass of pyrrole monomer is LiMn x Fe 1-x 0.15 times the mass of PO4, then obtain LiFe of PPy x Mn1-x PO4 (LiFe x Mn 1-x PO4@PPy);
[0106] (2) LiFe obtained in step (1) x Mn 1-x PO4@PPy was added to a 0.5 mol / L Li2SiO3 precursor solution, which was a mixture of tetraethyl silicate and lithium hydroxide. The solid-liquid ratio was controlled to be 1:25 and the reaction was continued for 0.5 h. After the solution was evaporated to dryness, LiFe in situ coated with Li2SiO3 was obtained. x Mn 1-x PO4@PPy (i.e. LiFe x Mn 1-x PO4@PPy@Li2SiO3);
[0107] (3) LiFe obtained in step (2) x Mn 1-x PO4@PPy@Li2SiO3, acetylene black, graphene, polyvinyl alcohol, and calcium chloride were ball-milled and mixed in a ratio of 1:0.10:0.05:0.04:0.5 for 6 h, and then NMP containing PVDF was added to the above mixture in three portions and mixed for 4 h to obtain a slurry, wherein PVDF is LiFe x Mn 1-x The mass of PO4@PPy@Li2SiO3 is 0.12 times, and NMP is 2 times the mass of all solids; the slurry is evenly coated on the titanium mesh and dried to obtain LiFe x Mn 1-x PO4@PPy@Li2SiO3 electrode.
[0108] A Li 1+y Fe x Mn 1-x Preparation of PO4@PPy@Li2SiO3 (0<x<1, 0<y<1) electrode: 1+y Fe x Mn 1-x The PO4@PPy@Li2SiO3 electrode was used as the cathode and the nickel foam was used as the anode. The cathode and cathode were placed in a LiCl solution containing a lithium concentration of 2 g / L. A voltage of 1.0 V was applied to both ends of the electrodes through an external circuit until the current density was lower than 0.5 A / m 2 , obtain Li 1+y Fe x Mn 1-x PO4@PPy@Li2SiO3 electrode.
[0109] Lithium extraction experiment: The electrochemical lithium extraction device was separated into a cathode chamber and an anode chamber using a monovalent anion selective permeable membrane. 1+y Fe x Mn 1-x PO4@PPy@Li2SiO3 electrode and LiFe x Mn 1-x PO4@PPy@Li2SiO3 electrodes were used as anode and cathode, and were placed in the anode chamber and cathode chamber, respectively. 30L of salt lake brine was injected into the cathode chamber. The main components of the brine used are shown in Table 3. 2L of 0.5g / L LiCl solution was injected into the anode as a supporting electrolyte. A voltage of 0.5V was applied to the cathode and cathode through an external circuit. After 5 hours of electrolysis, the lithium concentration of the brine decreased to 0.12g / L; the lithium concentration in the lithium-rich solution at the anode increased to 4.4g / L, the average current efficiency reached 89.98%, and the average current density was 34.31A / m 2 .
[0110] Table 3 Main components of brine used in Example 4
[0111] ion <![CDATA[Li + ]]> <![CDATA[Na + ]]> <![CDATA[K + ]]> <![CDATA[Ca 2+ ]]> <![CDATA[Mg 2+ ]]> <![CDATA[B4O7 2- ]]> Concentration (g / L) 0.38 36.29 7.07 23.25 10.75 3.14
[0112] Cyclic lithium extraction experiment: A diaphragm-free electrochemical lithium extraction device was used to conduct a cyclic lithium extraction experiment. 1+y Fe x Mn 1-x PO4@PPy@Li2SiO3 electrode and LiFe x Mn 1-x The PO4@PPy@Li2SiO3 electrodes were used as anode and cathode respectively and placed in a lithium extraction device. The power was turned on for a cyclic lithium extraction experiment. The cycle results showed that LiFe x Mn 1-x The PO4@PPy@Li2SiO3 electrode has good cycle stability. After 250 cycles, its capacity still reaches 26.88 mg / g, and the capacity retention rate is as high as 91.63%.
[0113] Example 5
[0114] A high stability electrode for electrochemical lithium extraction in this embodiment is prepared by the following method:
[0115] (1) Add LiFePO4 to 2 mol / L Li7La3Zr2O 12 (LLZO) precursor solution, the precursor solution is mixed with lithium acetate, lanthanum acetate and tetrabutyl zirconate in a stoichiometric ratio, the solid-liquid ratio is controlled to be 1:20 and the reaction is carried out for 5 hours, and the solution is evaporated to obtain LLZO in-situ coated LiFePO4 (i.e., LiFePO4@LLZO);
[0116] (2) mixing the LiFePO4@LLZO obtained in step (1) with the pyrrole monomer solution, and then dropping an oxidant, ferric chloride, to carry out polymerization reaction for 4 hours, wherein the mass of the pyrrole monomer is 0.1 times the mass of LiFePO4@LLZO, and then obtaining LiFePO4 double-coated with PPy and LLZO (i.e., LiFePO4@LLZO@PPy);
[0117] (3) The LiFePO4@LLZO@PPy obtained in step (2) was mixed with Ketjen black, carbon fiber, polyethylene glycol, and barium chloride in a ratio of 1:0.10:0.05:0.05:0.3 by ball milling for 5 hours, and then NMP containing PVDF was added to the above mixture in three portions. After fully mixing for 5 hours, a slurry was obtained, in which PVDF was 0.1 times the mass of LiFePO4@LLZO@PPy and NMP was 1.0 times the mass of all solids; the slurry was evenly coated on a titanium mesh and dried to obtain a LiFePO4@LL ZO@PPy electrode.
[0118] Li 1-x Preparation of FePO4@LLZO@PPy (0<x<1) electrode: The prepared LiFePO4@LLZO@PPy electrode was used as the anode and nickel foam as the cathode. The cathode and cathode were placed in a NaCl solution with a concentration of 20 g / L. A voltage of 1.0 V was applied to both ends of the electrode through an external circuit until the current density was lower than 0.5 A / m 2 , obtain Li 1-x FePO4@LLZO@PPy electrode.
[0119] Lithium extraction experiment: The electrochemical lithium extraction device was separated into a cathode chamber and an anode chamber using a monovalent anion selective permeable membrane. The prepared LiFePO4@LLZO@PPy electrode and Li 1-x FeBO3@Li 1-x The FePO4@LLZO@PPy electrodes were used as anode and cathode, respectively, and were placed in the anode chamber and cathode chamber, respectively. 30L of the same salt lake brine as in Example 2 was injected into the cathode chamber, and 2L of 5g / L NaCl solution was injected into the anode as a supporting electrolyte. A voltage of 0.3V was applied to the cathode and cathode through an external circuit. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density, and the average current efficiency are shown in Table 4.
[0120] Example 5-1
[0121] The method for preparing a high-stability electrode for electrochemical lithium extraction in this embodiment is the same as that in embodiment 5, except that the surface of the active material LiFePO4 is first coated with a conductive polymer polypyrrole (PPy), and then coated with Li7La3Zr2O 12 (LLZO).
[0122] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0123] Comparative Example 1
[0124] The high stability electrode for electrochemical lithium extraction in this comparative example is the same as that in Example 5, except that step (1) is removed, that is, in step (2), only PPy is coated on the surface of LiFePO4.
[0125] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0126] Comparative Example 2
[0127] The high stability electrode for electrochemical lithium extraction in this comparative example is the same as that in Example 5, except that step (2) is removed and only LLZO is coated on the surface of LiFePO4.
[0128] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0129] Comparative Example 3
[0130] The high stability electrode for electrochemical lithium extraction in this comparative example is the same as that in Example 5, except that in step (3), LiFePO4@LLZO@PPy is not pre-mixed with Ketjen black, carbon fiber, polyethylene glycol, and barium chloride by ball milling. Instead, a conventional pulping process is used to directly mix the raw materials to obtain a slurry.
[0131] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0132] Comparative Example 4
[0133] The preparation method of the electrode of this comparative example is as follows: directly slurry LiFePO4 with Ketjen black, carbon fiber, polyethylene glycol, barium chloride, and PVDF in a mass ratio of 1:0.10:0.05:0.05:0.3:0.1 using a conventional process, and the amount of NMP is the same as that in Example 5. The slurry is evenly coated on a titanium mesh and dried to obtain the electrode.
[0134] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0135] Comparative Example 5
[0136] The high stability electrode for electrochemical lithium extraction in this comparative example is the same as that in Example 5, except that in step (3), after ball milling and mixing, NMP containing PVDF is directly added to the above mixture at one time.
[0137] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0138] Comparative Example 6
[0139] The high stability electrode for electrochemical lithium extraction in this comparative example is the same as that in Example 5, except that in step (3), no pore-forming agent is added.
[0140] Lithium extraction was carried out under the same experimental conditions as in Example 5. After 6 hours of electrolysis, the lithium concentration of the brine, the lithium concentration in the anode lithium-rich solution, the average current density and the average current efficiency are shown in Table 4.
[0141] Table 4
[0142]
[0143] The electrodes prepared in Example 5, Example 5-1 and Comparative Examples 1-4 were subjected to cyclic lithium extraction tests: a diaphragm-free electrochemical lithium extraction device was used to perform cyclic lithium extraction experiments. The lithium-rich lithium iron phosphate electrode and the lithium-poor Li 1-x The FePO4 electrodes were used as anode and cathode respectively and placed in a lithium extraction device. Power was supplied to carry out a cyclic lithium extraction experiment.
[0144] Cycle performance Figure 3 As shown in Table 4 and Figure 3 It can be seen that the average current efficiency, average current density and cycle stability of the electrode prepared by the method of the present invention are effectively improved during the electrochemical lithium extraction process, and this optimization effect is the result of the synergistic effect of in-situ coating of solid electrolyte, conductive polymer coating and pre-mixed slurrying of electrode materials.
[0145] Compared with Example 5 and Example 5-1, the electrodes prepared in the two examples have good cycle performance and the difference is not large, which shows that the coating modification sequence of the active materials can be changed.
[0146] The inventor has also conducted the above experiments on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0147] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high stability electrode for electrochemical lithium extraction, characterized in that: It comprises a current collector, the surface of which is coated with an active material, a conductive agent, an additive and a pore-forming agent, and the active material is a polyanion material; The surface of the polyanion material is coated with a solid electrolyte and an organic conductive polymer in sequence from the inside to the outside; Or the surface of the polyanion material is coated with an organic conductive polymer and a solid electrolyte in sequence from the inside to the outside.
2. The high stability electrode for electrochemical lithium extraction according to claim 1, characterized in that: The solid electrolyte is at least one of garnet-type, peroxide-type, sodium superion conductor or lithium superion conductor solid electrolyte.
3. A high stability electrode for electrochemical lithium extraction according to claim 2, characterized in that: The solid electrolyte is Li7La3Zr2O 12 , Li 0.33 La 0.56 At least one of TiO3, LiTi2(PO4)3 or Li2SiO3.
4. A high stability electrode for electrochemical lithium extraction according to any one of claims 1 to 3, characterized in that: The organic conductive polymer is polymerized from conductive polymer monomers. Preferably, the conductive polymer monomer is at least one of pyrrole, aniline and thiophene.
5. A high stability electrode for electrochemical lithium extraction according to any one of claims 1 to 3, characterized in that: The polyanion material is a water-soluble lithium-ion battery material. Preferably, the polyanion material is LiFePO4OH, LiFePO4F, LiFe x Mn 1-x At least one of PO4 (0<x<1), LiFePO4.
6. A high stability electrode for electrochemical lithium extraction according to any one of claims 1 to 3, characterized in that: The conductive agent is at least one of acetylene black, carbon nanotubes, super P, Ketjen black, carbon fiber, and graphene; And / or, the additive is at least one of polyethylene glycol and polyvinyl alcohol; And / or, the pore-forming agent is at least one of sodium sulfate, potassium sulfate, magnesium chloride, magnesium sulfate, calcium chloride, and barium chloride.
7. A method for preparing an electrode according to any one of claims 1 to 6, characterized in that: The steps include: (1) mixing a polyanion material with a solid electrolyte precursor solution to react, and evaporating to obtain an active material in situ coated with a solid electrolyte; Or the polyanion material is mixed with the conductive polymer monomer, an oxidant is added to carry out polymerization reaction, and then dried to obtain an active material coated with an organic polymer; (2) mixing the active material coated in situ by the solid electrolyte with a conductive polymer monomer, adding an oxidant to carry out polymerization reaction, and drying to obtain a double-layer coated active material; or mixing the organic polymer coated active material with a solid electrolyte precursor solution to react and evaporate to obtain a double-layer coated active material; (3) Premixing the double-layer coated active material with a conductive agent, an additive, and a pore-forming agent, adding N-methylpyrrolidone dissolved with PVDF, mixing to obtain a slurry, and coating the slurry on a current collector to obtain the electrode.
8. The preparation method according to claim 7, characterized in that: In steps (1) and (2), the concentration of the solid electrolyte precursor solution is 0.1 to 3 mol / L.
9. The preparation method according to claim 7, characterized in that: In step (3), premix for 2 to 8 hours, add PVDF dissolved in N-methylpyrrolidone (NMP) in 3 to 5 portions, and mix for 2 to 6 hours.
10. The preparation method according to claim 7, characterized in that: In step (3), the mass ratio of the double-layer coated active material, the conductive agent, the additive, the pore-forming agent and the PVDF is 1:0.05-0.15:0.01-0.05:0.1-0.5:0.05-0.15.
Citation Information
Cited By
Polypyrrole coated solid electrolyte and preparation method thereof
CN120674572A
A polypyrrole-coated solid-state electrolyte and a preparation method thereof
CN120674572B